2019
DOI: 10.1093/nar/gkz164
|View full text |Cite
|
Sign up to set email alerts
|

Splice-Break: exploiting an RNA-seq splice junction algorithm to discover mitochondrial DNA deletion breakpoints and analyses of psychiatric disorders

Abstract: Deletions in the 16.6 kb mitochondrial genome have been implicated in numerous disorders that often display muscular and/or neurological symptoms due to the high-energy demands of these tissues. We describe a catalogue of 4489 putative mitochondrial DNA (mtDNA) deletions, including their frequency and relative read rate, using a combinatorial approach of mitochondria-targeted PCR, next-generation sequencing, bioinformatics, post-hoc filtering, annotation, and validation steps. Our bioinformatics pipeline uses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(66 citation statements)
references
References 55 publications
3
63
0
Order By: Relevance
“…High sequencing depth (Additional file 1 : Table S1) allowed the LostArc method to call roughly one deletion per million mtDNA circles (10 –5.9 ± 0.09 ; median ± 95% CL in the exponent). LostArc sensitivity exceeds that for sequencing after long-range PCR [ 39 ] but not for digital drop PCR (~ 10 −8 [ 35 , 40 , 41 ];). Unlike digital drop PCR, which targets deletions at specific loci, LostArc assays the full deletion spectrum across the whole mitochondrial genome.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…High sequencing depth (Additional file 1 : Table S1) allowed the LostArc method to call roughly one deletion per million mtDNA circles (10 –5.9 ± 0.09 ; median ± 95% CL in the exponent). LostArc sensitivity exceeds that for sequencing after long-range PCR [ 39 ] but not for digital drop PCR (~ 10 −8 [ 35 , 40 , 41 ];). Unlike digital drop PCR, which targets deletions at specific loci, LostArc assays the full deletion spectrum across the whole mitochondrial genome.…”
Section: Resultsmentioning
confidence: 99%
“…The latter found 451 unique deletions in human brain tissue. Recently, one high-throughput study found a remarkable 4489 unique deletions, in the brain and blood, by accepting the flaws of long-range PCR enrichment and eschewing absolute frequency measurements [ 39 ]. LostArc achieves mtDNA enrichment without long-range PCR amplification by selectively degrading linear nuclear DNA with nucleases (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Type I deletions are hypothesised to be formed by polymerase slippage during replication [ 50 ]. The discrepancy between human disease cases [ 51 ] and mouse models regarding direct repeats may relate to the different involvement of direct repeats in deletion formation between long-lived and short-lived mammals [ 26 ]. Type II deletions colocalize with 2D and 3D mtDNA structures [ 49 ] and occur spontaneously during replication either through strand slipping [ 48 ], Polg stalling [ 52 ], or repair of double-stranded breaks [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several methods have recently been developed specifically for identification of mtDNA deletions from high-throughput short read sequencing, including MitoDel [27], Splice-Break [28], eKLIPse [29], MitoMut [30], and a PERL script provided in (Zambelli et al, 2017) [31]. These methods rely on gapped alignments to predict deletions, but fail to recognize that every such event can represent either a deletion or a duplication affecting the arc complementary to the deleted part; a consequence of the circularity of mtDNA.…”
Section: Introductionmentioning
confidence: 99%